PENGARUH KUALITAS LABA AKUNTANSI TERHADAP EFISIENSI INVESTASI DENGAN RISIKO LITIGASI SEBAGAI VARIABEL MODERASI - Maryanto Maryanto; Irwan Muslim (Jurnal Ekonomi Sakti, 2023)
This study aims to find out: 1) Is there an Influence of the Quality of Accounting Profits on Investment Efficiency in Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2017-2021?, 2) Is there an Influence of Quality of Accounting Profits on Efficiency Investments with Litigation Risk as a Moderating Variable in Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2017-2021?, 3) Is there an Effect of Quality of Accounting Earnings on Litigation Risk as a Moderating Variable in Property and Sub-Sector Companies? Real Estate Listed on the Indonesia Stock Exchange (IDX) in 2017-2021 ? The population in this study were companies in the Property and Real Estate Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX), so a sample size of 60 respondents was obtained using a purposive sampling technique. The data analysis tool used is path analysis at an alpha level of 0.05. Based on the results of the study showed that: Accounting profit quality has no significant effect on investment efficiency. Litigation Risk weakens the Quality of Accounting Earnings on Investment Efficiency. Quality of Accounting Earnings does not significantly influence Litigation Risk.